Caregivers of Older Persons in Jamaica: Characteristics, Burden, and Associated Factors. (July 2021) - James, Kenneth; Thompson, Camelia; Holder-Nevins, Desmalee; Willie-Tyndale, Douladel; McKoy-Davis, Julian; Eldemire-Shearer, Denise
Objective: The objective of this study was to determine and characterize caregiver burden among caregivers of community-dwelling older persons in Jamaica. Method: A nationally representative cross-sectional study was done among persons providing noninstitutional care for a single person (≥60 years). The Zarit Burden Interview (ZBI) and a structured questionnaire were administered to 180 caregivers from four geographic health regions. Results: The ZBI scores ranged from 0 to 56 (median = 15). Independently associated factors were relationship to care recipient and age. Children/grandchildren had higher caregiver burden scores than formally employed caregivers (odds ratio = 2.9: 95% confidence interval: [1.02, 8.34]). Compared with caregivers 35 to 44 years, those aged 45 to 65 were almost 5 times more likely to report higher caregiver burden scores. Conclusion: Caregiver burden as identified by the ZBI was low. Age (45–65 years) and being the child/grandchild of the care recipient were independently associated with greater caregiver burden. Interventions to address caregiver burden must embrace strategies that recognize that these factors.